Zmiana uwarunkowań hydrogeologicznych wskutek eksploatacji węgla brunatnego w zlewni Nysy Łużyckiej = The change of hydrogeological conditions due to lignite exploitation in Nysa Łużycka catchment - Kołodziejczyk, Urszula (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
There are a lot of brown coal deposits in Nysa Łużycka catchment. Until now their exploitation has caused a substantial changes in natural environment, such as ground water table lowering. The inhabitants of the region oppose further exploitation pointing out the gradual loss of water in wells and degradation of the agricultural land.
Keywords: węgiel brunatny - eksploatacja; rekultywacja; hydrogeologia; lignite; reclamation; hydrogeology